DIMENSI SUFISTIK SURAT AL-WAQI’AH: STUDI KITAB LATAIF AL-ISHARAT KARYA IMAM AL-QUSHAYRI - Arif Budiono (Institut Keislaman Abdullah Faqih Gresik, 2022)
Abstract: The tradition of reading surah al-Waqi'ah became a Living Qur'an that lived in the midst of society. Worldly motivations are a foundation that is often misinterpreted. This is inseparable from some transcendent nash who expose the urgency of reading this letter which is reciprocated with the enjoyment of the world, so that some muslims make routine. On the other hand, worship must be based on the nature of sincerity as a condition for acceptance of worship charity. There are several sufistic dimensions recorded by the tafsir literature both classical and modern, especially the interpretation of Lataif al-Isharat whose author, al-Imam al-Qushayri is considered an influential interpretive figure in the 5th century A.D., especially his thought of restoring Sufism to the values of the Qur'an and the hadith of the Apostle Saw. The word al-waqi'ah is a condition of the soul reaching a higher maqam after experiencing wandering and purifying the soul, through various methods such as riyadah, tafakkur, tazakkur and tazkiyah al-nafs. A salik who reaches a mortal state', where high consciousness and memory are addressed only to Allah Swt., is characterized by the loss of the nature of the psalm (despicable) in the self and replaced the nature of mahmudah (praiseworthy), based on a strong concern for the tadbir (deeds) of Allah Swt, for all he hears is Allah Swt, to Allah Swt. (fillah), with Allah Swt. (billah) and from Allah Swt. (minallah) in the hereafter (as closeness). The word al-muqarrabun is understood by the proximity of a salik to al-Haqq, these are the properties of the heart, not the laws that are natural phenomena. As for muqarrabun in the context of the afterlife, it is a testimony, appearance and awareness of the existence of the lutfi form (the tenderness of God and His grace). The essence of charity and human deeds comes from the Supreme Creator. The word bertasbih whose lexical meaning is ta'ajjub, can be interpreted as a sense of awe of the various favors revealed and the noble position of Allah Swt., the form of prayer beads can be intended as a manifestation of the expression of gratitude and tanzih (purifying) the dzat of Allah Swt. of all forms. In consecration should always use the potential of critical thinking and reasoning, based on a sense of submission in the power of tawhid, then Allah Swt. will open the curtain of the hidden pearls of science. The word lams not only touches sensory, but can be understood all interactions with the Qur'an. While the word mutahharun can also be read mutahhirun, meaning that those who can interact with the Qur'an, whose heart is holy from hadas (tendency to follow the shahwat), do not perform toxicity so as to achieve maqam rabbaniyyah ilahiyyah. Therefore, the Qur'an makruh is read from an unclean mouth (resulting from maksiat in words), and does not take advantage of the world from the recitation of the Qur'an, because its main principle is to glorify and glorify the Qur'an. Keyword: sufistik, surah Al-Waqi'ah, Imam al-Qushairy